Inverse reasoning processes in obsessive-compulsive disorder: Replication in a clinical sample. (April 2019) - Wong, Shiu F.; Aardema, Frederick; Grisham, Jessica R.
Highlights: This study tested the central tenet of the inference-based model of OCD. We compared clinical groups on a novel task-based measure of inverse reasoning. Individuals with OCD scored higher on inverse reasoning relative to clinical and healthy controls. Findings support a specific relationship between inverse reasoning and OCD. Abstract: The inference-based approach (IBA) is one cognitive model that aims to explain the aetiology and maintenance of obsessive-compulsive disorder (OCD). IBA theory suggests that certain reasoning processes lead an individual with OCD to confuse imagined possibilities with actual probabilities, a process termed inferential confusion. One such reasoning process is inverse reasoning, where hypothetical causes form the basis of conclusions about reality. Recently, we developed a task-based measure of inverse reasoning. In an online sample, we reported significant and positive associations between endorsement of inverse reasoning on this task and OCD symptomatology. We concluded that there was some support for the role of inverse reasoning in OCD but these results required extension using a between-groups design in a clinical sample. Therefore, the present study compared endorsement in inverse reasoning on this task between individuals diagnosed with OCD, anxiety and/or mood disorder (clinical controls), and healthy individuals (healthy controls). Relative to both control groups, the OCD group demonstrated significantly greater endorsement in inverse reasoning on scenarios where OCD relevant concerns were prompted. When non-OCD relevant concerns were involved, the OCD group only evidenced greater endorsement in inverse reasoning relative to the healthy control group. Implications for IBA theory are discussed.